Evaluasi Tingkat Kesukaan Terhadap Sifat Organoleptik Susu Kambing Pasteurisasi Yang Diberi Berbagai Tingkat Ekstrak Jambu Biji Merah (Psidium guajava L.) - Rifki Ahmad Fachrezi; Dini Widianingrum; Oki Imanudin (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2023)
The aim of this research is to analyze the effect of adding red guava extract on the level of consumer preference for organoleptic properties including color, aroma, viscosity level, taste and taste of pasteurized goat's milk. This research used an experimental method with a Completely Randomized Design (CRD) pattern consisting of 5 treatments and 4 replications. The treatment used was the addition of red guava extract (P0= milk without red guava extract, P1= milk + 3%, P2= milk + 6%, P3= milk + 9% and P4 milk + 12%). The data obtained were analyzed using analysis of variance (ANOVA) and if the results of the anova test showed that there were significant differences, Duncan's further test was carried out. The results of the research showed that the addition of red guava extract to the manufacture of pasteurized goat's milk had an effect on the level of preference for organoleptic characteristics (color, viscosity level, aroma, flavor and taste). The best counter treatment is the addition of 6% red guava extract with the criteria of yellowish white color, pleasant aroma, light viscosity, sweet taste, slightly savory taste and a liking level of slightly like to like. 6% red guava extract produced the best level of favorability.